Potential of Corn Stalk Biomass as Biosorbent in Adsorption of Mercury (Hg) Metal Contaminants - Fathurrahman, Muhammad; Sutanto, Sutanto; Sukresna, Yobi (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
Corn stalks are an agricultural waste that is commonly found in Indonesia. Corn stalks have a high enough cellulose content which has functional groups that can be used as biosorbents. This study aims to optimize the adsorption of corn stalk waste to mercury metal ions and then determine the adsorption capacity and adsorption constant of the Langmuir and Freundlich isotherm model. This research begins with corn stalk preparation, delignification, characterization using FTIR and SEM, determination of optimization of biosorbent weight, pH of Hg solution, contact time, and concentration of Hg solution, then applied to mercury metal contamination waste. Optimization of the weight of biosorbent in the range 0.4-1.2 grams, pH of the Hg solution is 2-4, contact time is 60-120 minutes, and concentration of the Hg solution of 30-100 g/L with a solution volume of 50 mL. Furthermore, determination of mercury levels, manufacture of standard series, and testing using ICP-OES. Followed by the determination of Langmuir and Freundlich's adsorption isothermal model. The results of this study indicate that the optimum conditions for the adsorption process occur at the weight of the biosorbent 1.2 grams, pH of the Hg 3 solution, contact time of 90 minutes, and concentration of Hg solution of 40 ppb with a solution volume of 50 mL. The application of biosorbent to metal contamination waste with adsorbed Hg concentration obtained 27.5772 ppb in 50 mL of waste solution with an adsorption efficiency of 88.44%. In the determination of Langmuir and Freundlich isotherms, a match was found for Langmuir adsorption isothermals with an adsorption capacity of 0.00333 mg Hg/g biosorbent and b = 176.8256.